Alterations in circadian rhythms of melatonin and cortisol in patients with bronchial asthma - FEI Guang-he; LIU Rong-yu; ZHANG Zhi-hong; ZHOU Jiang-ning (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the possible relationships between alterations in circadian rhythm of melatonin, cortisol and bronchial asthma. METHODS: Salivary melatonin and cortisol were measured simultaneously by radioimmunoassay in 10 mild intermittent or persistent patients, 11 moderate-to-severe persistent asthma patients, and 15 control subjects. Twelve salivary samples were collected in a series during a 24-h period in each subject. RESULTS: The results showed overall lower levels of salivary melatonin in asthma patients compared with control subject (P